Elimination of Industrial Textile Dye by Electrocoagulation Using Iron Electrodes - Salazar-Gonzalez, R; Vidal-Fuentes, J; Vidal-Fuentes, J; Espinoza-Cisternas, L; Espinoza-Cisternas, L (Sociedad Chilena de Quimica, 2017)
Electrocoagulation is a promising technique for the treatment of wastewater like the produced by the textile industry, which generates large volumes of water containing dyes. Thus, synthetic samples of the textile dye acid black 194 (AB194, CI 22910) were treated by this method using iron anodes at two different initial pH values. Tafel studies in the presence and absence of the dye were performed. The complete removal of AB194 from 1.0 L of solution in a static cell was achieved, at short electrolysis times, applying low-density currents at two different initial pH values. In addition, the operating costs by mass consumed anode, per cubic meter electocoagulated and per TOC unit, were assessed to help determine the most efficient conditions, considering a future application of the method in the industry.